PENGARUH KEJENUHAN KERJA DAN KOMPETENSI MANAJERIAL TERHADAP KINERJA KEPALA SEKOLAH SMP SWASTA SE-KOTA PEKANBARU - Yenti Widiastuti; Fadly Azhar; Hasnah Faizah AR (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effect of job burnout and managerial competency on the performance of private junior high school principals in Pekanbaru, Riau Province. The study used a quantitative correlational research design involving 83 school principals. Data were analyzed using simple and multiple linear regression techniques. The results showed that job burnout significantly affected principals’ performance (Fcount = 21.484 > Ftable = 3.96, p < 0.05), and managerial competency also had a significant effect (Fcount = 93.401 > Ftable = 3.96, p < 0.05). Furthermore, job burnout and managerial competency simultaneously influenced principals’ performance (Fcount = 60.177 > Ftable = 3.11, p < 0.05), accounting for 60.1% of the variation, with the remaining 39.9% attributed to other factors.